1988
DOI: 10.1172/jci113653
|View full text |Cite
|
Sign up to set email alerts
|

Site and mechanism of action of trichlormethiazide in rabbit distal nephron segments perfused in vitro.

Abstract: To determine the exact site and mechanism of action of thiazide diuretics, effects of 104 M trichlormethiazide (TCM) on NaCJ transport were examined in the distal convoluted tubule (DCT), the connecting tubule (CNT) and the cortical collecting duct (CCD) of rabbit kidney by the in vitro microperfusion technique. TCM added to the lumen decreased lumen-to-bath 'Cl flux (JC(LB)) only in the CNT without changing the transmural voltage (VT). In the DCT, 10-4 M furosemide did not change JCI(LB) even if it was added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…Thus, relative hypocalciuric effect of S-8666 (Shimizu et al 1989a) may be explained also by its action on the CNT. Since we have also demonstrated that furosemide did not affect Cl-transport in the CNT (Shimizu et al 1988c), the additive diuretic effect of S-8666 and furosemide (Shimizu et al 1989b) may be accounted for by the action of S-8666 on the CNT.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Thus, relative hypocalciuric effect of S-8666 (Shimizu et al 1989a) may be explained also by its action on the CNT. Since we have also demonstrated that furosemide did not affect Cl-transport in the CNT (Shimizu et al 1988c), the additive diuretic effect of S-8666 and furosemide (Shimizu et al 1989b) may be accounted for by the action of S-8666 on the CNT.…”
Section: Discussionmentioning
confidence: 58%
“…In the previous study (Shimizu et al 1988c), we have established that in the rabbit thiazide diuretics inhibit Na+-C1-cotransport by acting exclusively on the ONT. Neither distal convoluted tubule (DOT) nor cortical collecting duct (COD) is the target of the action of thiazide diuretics.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations